Program Shalat Subuh Berjamaah dan Kesadaran Beragama - Murti, Siti; Heryanto, Heryanto (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2022)
This research is focused on the purpose of analyzing congregational prayer as a means of education to increase religious awareness in a person, in order to obtain an overview of the process, patterns and factors that influence it. This research was conducted using a qualitative approach. The method of determining the sample using purposive sampling technique, and key informants with snowball sampling technique, while the sample size is determined based on the completeness of the required information. Overall the number of participants involved as participant respondents was 15 people. Research data were collected through observation, interviews, and documentation. Fajr prayer in congregation at the mosque as a place of research, because the Fajr prayer in congregation has its own advantages and challenges compared to other fardhu prayers. The results showed that the process of developing one's religious awareness lasts a lifetime. The family is the first educational institution that teaches religious awareness to someone from the time they are in the womb. Educational institutions, and community education are also factors that influence the increase in religious awareness. The process of developing religious awareness in a person is not the same (diverse) and is not always stable. Congregational prayer is seen as a means to increase religious awareness. In general, an established religious awareness is obtained after the age of 40 years, and the background of religious awareness in childhood also determines religious awareness as an adult.